2019
DOI: 10.5935/2359-4802.20190034
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hospital Accreditation Process in Outcomes of Patients with Acute Coronary Syndrome

Abstract: Background: Hospital accreditation has as goal the standardization of patient care, aiming quality improvement. On 2015, a cardiology reference hospital was evaluated and got level 3 from ONA in care given to Acute Coronary Syndrome (ACS) patients.Objetive: To compare length of stay (LOS) at Coronary Care Unit (CCU) and the total LOS at the hospital of ACS patients before and after ONA 3 accreditation. Other clinical outcomes were also analyzed.Methods: Systematic and prospective registry of admitted ACS patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Several studies consistently indicated a lack of relationship between accreditation and hospital 30-day readmission rate in various contexts [ 21 , 84 , 89 , 90 ], whereas other studies presented contradictory effects on healthcare-associated infections [ 25 , 85 , 91 , 92 ]. However, studies reported a consistently positive impact of accreditation on hospital [ 84 , 86 , 89 , 93 ] and departmental [ 91 , 94 , 95 ] patient length of stay.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies consistently indicated a lack of relationship between accreditation and hospital 30-day readmission rate in various contexts [ 21 , 84 , 89 , 90 ], whereas other studies presented contradictory effects on healthcare-associated infections [ 25 , 85 , 91 , 92 ]. However, studies reported a consistently positive impact of accreditation on hospital [ 84 , 86 , 89 , 93 ] and departmental [ 91 , 94 , 95 ] patient length of stay.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, around one third (n = 24) of the included studies examined the impact of hospital accreditation on patient outcomes [8,21,25,[50][51][52][53][79][80][81][82][83][84][85][86][87][88][89][90][91][92][93][94][95]. Of these, 75% have been published since 2015 as an obvious response to previous appeals to investigate accreditation effects on clinical outcomes.…”
Section: Changes In Patient Clinical Outcomesmentioning
confidence: 99%
“…Interestingly, around one-third (n = 24) of the included studies examined the impact of hospital accreditation on patient outcomes [20,33,38,61,71,90,91,92,[118][119][120][121][122][123][124][125][126][127][128][129][130][131][132][133]. Of these, 75% have been published since 2015 as an obvious response to previous appeals to investigate accreditation effects on clinical outcomes.…”
Section: • Changes In Patient Clinical Outcomesmentioning
confidence: 99%
“…Several studies consistently indicated a lack of relationship between accreditation and hospital 30-day readmission rate in various contexts [20,123,127,128], whereas other studies presented contradictory effects on healthcare-associated infections [38,124,129,130]. However, studies reported a consistently positive impact of accreditation on the hospital [33,123,127,131] and departmental [129,132,133] patient length of stay.…”
Section: • Changes In Patient Clinical Outcomesmentioning
confidence: 99%